Liana assemblage structure in four sites across the Brazilian Amazon - Nogueira, Anselmo; Costa, Flávia Regina Capellotto; Vilela-Santos, Márcia Cléia; Castilho, Carolina Volkmer; Andrade, Ana C.S.; Camargo, José Luís Campana; Laurance, William F.; Burnham, Robyn Jeanette (Ecology of Lianas, 2014)
This chapter presents a study conducted on four sites in the Brazilian Amazon. These sites were used without evidence of recent anthropic impact, to sample liana and tree density and basal area (BA). Lianas were sampled at all four sites following the protocols suggested by Gerwing et al., in which only lianas rooted within each plot were sampled. ANOVA was used to test whether liana density, liana basal area, and the ratio of lianas to trees differed among sites. Although the distribution pattern of lianas on a global scale has been related to climatic variables, such as seasonality and precipitation, contrasting results suggest the need for new data for a more detailed description of vegetation structure throughout tropical forests. The results provide additional evidence of the association between climatic variables and the variation in liana density and BA in Amazonian forests and are consistent with Schnitzer, DeWalt et al.. © 2015 by JohnWiley & Sons, Ltd. All rights reserved.